Extracellular Vesicles as Carriers of Non-coding RNAs in Liver Diseases - Yang, Junfa; Li, Changyao; Zhang, Lei; Wang, Xiao (Frontiers in Pharmacology, 2018)
Extracellular vesicles (EVs) are small membranous vesicles secreted from normal, diseased, and transformed cells in vitro and vivo. EVs have been found to play a critical role in cell-to-cell communication by transferring non-coding RNAs (ncRNAs) including microRNAs (miRNAs), long non-coding RNAs (lncRNAs) and so on. Emerging evidence shows that transferring biological information through EVs to neighboring cells in intercellular communication not only keep physiological functions, but also participate in the pathogenesis of liver diseases. Liver diseases often promote release of EVs and/or in different cargo sorting into these EVs. Either of these modifications can promote disease pathogenesis. Given this fact, EV-associated ncRNAs，such as miR-192, miR-122 and lncRNA-ROR and so on, can serve as new diagnostic biomarkers and new therapeutic targets for liver disease, because altered EV-associated ncRNAs may reflect the underlying liver disease condition. In this review, we focus on understanding the emerging role of EV-associated ncRNAs in viral hepatitis, liver fibrosis, alcoholic hepatitis (AH), non-alcoholic steatohepatitis (NASH) and hepatocellular carcinoma (HCC) and discuss their utility in biomarker discovery and therapeutics. A better understanding of this multifaceted pattern of communication between different type cells in liver may contribute to developing novel approaches for personalized diagnostics and therapeutics.